UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI PERMAINAN FLASH CARDS PADA ANAK KELOMPOK B DI DI TK ISLAM BAKTI I GAGAKSIPAT TAHUN 2018/2019 - Isnaini, Yustika (CV Sintesia, 2024)
The purpose of this study was an effort to improve cognitive abilities in the children of the Islamic Kindergarten B group I gagaksipat Boyolali regency by using flash card games. This study uses a classroom action research approach. The objects of this research are the 17 children of group b Islamic Kindergarten I Gagaksipat. The type of research used in this research is classroom action research. Classroom action research was carried out in two cycles. The research procedure consists of four stages, namely action planning, action implementation, observation and reflection. The data collection technique used is observation. Based on the results of the study, it can be concluded that children's cognitive abilities have increased. This is indicated by an increase in the pre-cycle of 40.2%, increasing to 73% in the first cycle, then increasing again in the second cycle to 86.4%. Thus, the use of flash card games can improve cognitive abilities in children in group B of Islamic Kindergarten I Gagaksipat, Boyolali Regency.